Penguatan Pola Asuh Positif Bagi Orang Tua dalam Pemenuhan Hak Anak di Era Digital - Abbas, Hafid; Purnama Dewi, Intan; BR. Dalimunthe, Henny Herawaty; Hutama Putra, Nararia (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
In the digital era, challenges in fulfilling children's rights have become increasingly complex. Technological advancements, along with social and economic changes, bring both positive and negative impacts on children's lives. On the one hand, technology provides children with broad access to information and learning opportunities; on the other hand, it also poses risks such as addiction, exposure to negative content, and cyberbullying. Therefore, it is important for parents to remain literate regarding current developments and to possess adequate knowledge and understanding. Bogor Regency has a high rate of early marriage and young-age divorce cases. This phenomenon also occurs in Sukaharja Village, where early marriage and young-age divorce have become common occurrences. In fact, these conditions constitute forms of violations of children's rights. In addition, nutritional deficiencies that hinder children’s optimal development remain a significant issue. Consequently, transformative efforts are needed through counseling and assistance programs for parents regarding positive parenting and children’s rights. The community service program conducted in Sukaharja Village targeted parents with early childhood and school-age children, who were divided into four groups consisting of eight participants in each group. The evaluation results showed an average increase in understanding of 46.3% from pretest to posttest. The science and technology products developed included educational modules, learning videos, and infographics, all of which were well received and have the potential to become sustainable learning resources for the community. The establishment of parent discussion groups through WhatsApp and regular meetings in Sukaharja Village, along with the village government’s commitment to adopting the materials into routine activities such as Posyandu and PKK meetings, demonstrates the sustainability potential of the program.